Performance Measurement Analysis of Sustainable Supply Chain Management Using the AHP-Based SCOR Method and OMAX at PT XYZ - Tauriza Alfiane, Revica; Ernawati, Dira; Nugraha , Isna (Journal of Research and Technology, 2025)
The manufacturing industry faces many challenges in continuing to compete with its competitors. These challenges come from various aspects, namely economic, social, and environmental. One approach to fixing this problem is to use effective SCOR, AHP, and OMAX methods. PT XYZ is a sugar company that has never measured sustainable supply chain performance. In connection with this, many studies have measured the performance of the sustainable supply chain. This research aims to improve the performance of Sustainable Supply Chain Management (SSCM) in production activities carried out by PT. XYZ so that the production process runs well and still pays attention to the sustainability aspects that must be implemented. A total of nineteen key performance indicators (KPIs) were generated by the five SCOR models used in data processing (plan, source, make, deliver, and return). There are seventeen key performance indicators with green indicators and two yellow indicators. With a final score of 8,022 on the sustainable supply chain performance level, this value is included in the green category which shows the company has successfully implemented the concept of sustainability in its business line.